Trading stocks on blocks: The quality of decentralized markets - Benedikt Notheisen; Vincenzo Marino; Daniel Englert; Christof Weinhardt (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2019)
The trust-free nature of blockchain-based systems challenges the role of traditional platform providers and enables the creation of new, intermediary-free markets. Despite the growing number of such markets, the impact of the blockchain's configuration on market outcomes remains unclear. In this study, we utilize order-level data from realworld financial markets to explore the impact of the blockchain parameters block size and block creation time on the quality of decentralized markets. More specifically, we find that increasing the blocks' capacity improves market activity, while higher block frequencies impose a trade-off between higher turnovers and lower trade sizes. In addition, we identify the block creation time and block size as core drivers of daily and intraday liquidity, respectively. In consequence, improving liquidity goes hand in hand with a higher activity. However, the reciprocal relationship between blockchain parameters and the increasing price impact of a block also indicate that faster and bigger blocks are no silver bullet to scale decentralized markets and may facilitate volatility. In total, we contribute an initial, technology-agnostic assessment of the quality of decentralized markets that aims to guide interdisciplinary researchers and innovative practitioners.
urn:nbn:de:swb:90-924853
Keywords: D47; G14; L86; N2; O16; 330; Decentralized markets; Blockchain; Market quality; Market design; Market engineering; FinTech